Cataloguing and characterizing interests in typically developing toddlers and toddlers who develop ASD. Issue 8 (22nd May 2021) - Burrows, Catherine A.; Bodfish, James W.; Wolff, Jason J.; Vollman, Elayne P.; Altschuler, Melody R.; Botteron, Kelly N.; Dager, Stephen R.; Estes, Annette M.; Hazlett, Heather C.; Pruett, John R.; Schultz, Robert T.; Zwaigenbaum, Lonnie; et al.
Abstract: Intense interests are common in children with and without autism spectrum disorder (ASD), and little research has characterized aspects of interests that are unique to or shared among children with and without ASD. We aimed to characterize interests in a sample of infants at high‐familial‐risk (HR) and low‐familial‐risk (LR) for ASD using a novel interview. Participants included HR siblings who were diagnosed with ASD at 24 months (HR‐ASD, n  = 56), HR siblings who did not receive an ASD diagnosis at 24 months (HR‐Neg, n  = 187), and a LR comparison group ( n  = 109). We developed and collected data with the Intense Interests Inventory at 18‐ and 24‐months of age, a semi‐structured interview that measures intensity and peculiarity of interests in toddlers and preschool‐aged children. Intensity of interests differed by familial risk at 24 months, with HR‐ASD and HR‐Neg groups demonstrating equivalent intensity of interests that were higher than the LR group. By contrast, peculiarity of interest differed by ASD diagnosis, with the HR‐ASD group showing more peculiar interests than the HR‐Neg and LR groups at 24 months. At 18 months the HR‐ASD group had more peculiar interests than the LR group, though no differences emerged in intensity of interests. This measure may be useful in identifying clinically‐relevant features of interests in young children with ASD. We also replicated previous findings of males showing more intense interests at 18 months in our non‐ASD sample. These results reveal new information about the nature of interests and preoccupations in the early autism phenotype. Lay summary: Intense interests are common in young children with autism and their family members. Intense interests are also prevalent among typically‐developing children, and especially boys. Here we catalog interests and features of these interests in a large sample of toddlers enriched for autism risk. Children who had family members with autism had more intense interests, and those who developed autism themselves had more unusual interests at 24 months. These results highlight the importance of different aspects of interest in autism.